Strict biennial lifecycle and anthropogenic interventions affect temporal genetic differentiation in the endangered endemic plant, Pedicularis hallaisanensis - Kim, Seongjun; Lee, Byoung-Doo; Lee, Chang Woo; Park, Hwan-Joon; Hwang, Jung Eun; Park, Hyeong Bin; Kim, Young-Joong; Jeon, Daeyoung; Yoon, Young-Jun (Frontiers in Plant Science, 2024)
Strict biennials are among the least known lifecycles in plant ecology due to their rarity in nature, and their population genetics still remain unknown. The present study addressed the strict biennial lifecycle and associated population genetics of Pedicularis hallaisanensis, an endangered endemic plant in Korea. All P. hallaisanensis individuals were counted in August from 2021 to 2023 in the wild population of Gayasan National Park, and lifecycle and morphological changes were monitored monthly. A de novo draft genome and single nucleotide polymorphism (SNP) analysis were used to study the population’s genetic structure. P. hallaisanensis strictly requires a 2-year lifecycle per generation, including 8 and 10 months of growing periods as a first-year seedling and second-year adult, respectively. Facultative annual and perennial lifecycles were undetected, resulting in odd-year and even-year flowering cohorts. Permutational multivariate analysis of variance on the detected 3,716 SNPs demonstrated that the flowering group (p < 0.005), microhabitat (p < 0.001), and their interaction (p < 0.01) had a significant effect on genetic structure, which was differentiated between odd-year and even-year flowering cohorts. Other cluster analyses also showed that a microhabitat under historical anthropogenic interventions contained lowered genetic diversity due to a decreased genetic distance between odd-year and even-year flowering cohorts (p < 0.05). Overall, the findings suggest that excessive anthropogenic interventions should be avoided to preserve genetic diversity in the wild P. hallaisanensis population. Moreover, conservation programs for similar biennial plants should collect wild breeds from both odd-year and even-year flowering cohorts to improve the genetic diversity of artificially propagated individuals.